Design of Bus Depot Terminal Element Consideration for Safe and Effective Infrastructure. Issue 1 (April 2021) - Rajeshkumar, V.; Logeswaran, S.; Selvaraj, R.; Abishek,; Dharshini, Devi; Aravind,; Dhivakar,
Abstract: Bus transport in India is the main mode of transport in the 21st century for both intercity and interstate services. NUTP (National Urban Transport Policy) 2006 focussed the development of bus transport in Indian cities. They developed JNNURM policy for improving intercity bus services. Large part of bus transport is catered by private sector in 2020 than government sector in India. Without improving the level of service in depot areas, the bus accessibility and operational efficiency cannot be achieved. In order to improve the LOS certain strategy has to be followed in depot elements such as depot infrastructure improvement, planning guidelines for platform infrastructure, and design elements for achieving the increased LOS. This paper explains the standards for individual element in Bus depot to be followed for effective utilisation and functioning of facilities provided. The specific guidelines, standards and toolkits are the most effective format for capacity building in an organisation. It also facilitates low cost with rapid sharing of knowledge and experience. Additionally, no stake holder requirement is overlooked and ensures the minimum standards of development.